A Systematic Review of Older Adults' Attitudes Towards Depression and Its Treatment. (22nd May 2019) - Nair, Pushpa; Bhanu, Cini; Frost, Rachael; Buszewicz, Marta; Walters, Kate R
Abstract: Background and Objectives: Late-life depression is a major societal concern, but older adults' attitudes toward its treatment remain complex. We aimed to explore older adults' views regarding depression and its treatment. Research Design and Methods: We undertook a systematic review and thematic synthesis of qualitative studies that explored the views of older community-dwelling adults with depression (not actively engaged in treatment), about depression and its treatment. We searched 7 databases (inception–November 2018) and 2 reviewers independently quality-appraised studies using the CASP checklist. Results: Out of 8, 351 records, we included 11 studies for thematic synthesis. Depression was viewed as a normal reaction to life stressors and ageing. Consequently, older adults preferred self-management strategies (e.g., socializing, prayer) that aligned with their lived experiences and self-image. Professional interventions (e.g., antidepressants, psychological therapies) were sometimes considered necessary for more severe depression, but participants had mixed views. Willingness to try treatments was based on a balance of different judgments, including perceptions about potential harm and attitudes based on trust, familiarity, and past experiences. Societal and structural factors, including stigma, ethnicity, and ageism, also influenced treatment attitudes. Discussion and Implications: Supporting older adults to self-manage milder depressive symptoms may be more acceptable than professional interventions. Assisting older adults with accessing professional help for more severe symptoms might be better achieved by integrating access to help within familiar, convenient locations to reduce stigma and increase accessibility. Discussing treatment choices using narratives that engage with older adults' lived experiences of depression may lead to greater acceptability and engagement.